The Effect of Providing Education on Anxiety In Patients with Acute Myocardial Infarction (AMI) at Prof. Dr. Margono Soekarjo Hospital - Bekti Kusumaning Tyas; Adiratna Sekar Siwi; Septian Mixrova Sebayang (Viva Medika, 2023)
Acute Myocardial Infarction (AMI) is one of the cardiac diseases that can arise when blood flow in the coronary artery is restricted, depriving the heart muscle of oxygen. Anxiety is a common mental health problem in Acute Myocardial Infarction (AMI) patients. One of the many treatments for anxiety that is accessible is using educational programs. Prevention, medical care, and lifestyle modifications like nutrition, stress reduction, exercise, and quitting smoking are all covered in the health education offered. This study aims to determine whether providing educational programs has an effect on individuals with acute myocardial infarction (AMI) in terms of anxiety. With a sample size of 44 participants, both intervention and control groups received education in the form of a 5-minute video as part of the study's Quasy Experimental Nonequivalent Control Group research design. The State Trait Anxiety Inventory (STAI), a questionnaire comprising 40 statement questions, was the instrument employed in this investigation. The findings of this study indicate that there is an impact of educational programs on anxiety in acute myocardial infarction (AMI) patients (P=0.042 0.05).